Feeding Time and Agonistic Behavior in Horses: Influence of Distance, Proportion, and Height of Troughs - Luz, Marina P. P. [UNESP]; Maia, Caroline M. [UNESP]; Pantoja, Jose Carlos E. [UNESP]; Neto, Marcos Chiquitelli [UNESP]; Puoli Filho, Jose Nicolau P. [UNESP] (Elsevier B.V., 2015)
Horses express social-based organizations when grouped and also show conflicts over resources, which can progress to agonistic interactions. The domestication led horses to be fed in confinement, which may have had increased the competition for food. We tested whether the distance, height of positioning, and proportion of feeding troughs affect the agonistic behavior in horses, and whether such effects are influenced by the social stability. We simultaneously varied these three factors at two levels (eight treatments). The group of horses (n = 8) was subjected to all treatments in a primary phase (no previous experience of feeding ration together) and in a secondary phase (social relationships better established by the agonistic interactions in the primary phase). In each treatment, we recorded agonistic behaviors during 30 minutes while horses were feeding. A distance of 10 m and a height of 0.71 m of the troughs reduced kick behavior, regardless of the phases evaluated. For agonistic signaling pinned back ears behavior, initially, a far distance (10 m), low positioning (0 m of height), and a greater proportion of feeding troughs (1.5 per horse) reduced this behavior. However, in the secondary phase, the effect of distance was consistent, but the effects of height positioning and proportion were opposite. Moreover, pinned back ears was the most frequent agonistic behavior. We conclude that the effect of height and proportion of troughs on agonistic behaviors of horses may depend of the social stability, whereas a far distance between troughs reduces the most frequent agonistic behavior, regardless of such social homeostasis. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Horse; Feeding; Trough; Agonistic behavior; Pinned back ears